Biodiversity of parasites infecting Bothrops erythromelas amaral, 1923 (Squamata, Viperidae): an endemic venomous snake species from the Brazilian Northeast - Leite Matias, Cicera Silvilene (2024)
The knowledge of parasitic fauna in wild animals is essential for understanding the ecological conditions that determine the occurrence and prevalence of parasites in their hosts. With the exception of records of one Pentastomida (Cephalobaena tetrapoda Heymons, 1922) and two Nematoda (Physaloptera sp. And Aspiculuris sp.), detailed information about the helminth fauna associated with the jararaca Bothrops erythromelas Amaral, 1923 is lacking. This species has a wide distribution in the Caatinga, with records in marginal areas of the Cerrado and Atlantic Forest. Here, we describe the patterns of richness, abundance, and prevalence of helminths in B. erythromelas, a venomous snake from northeastern Brazil. The parasitized snakes were collected from six Brazilian states in the Northeast region: Bahia, Ceará, Paraíba, Pernambuco, Piauí, and Rio Grande do Norte. We examined the gastrointestinal tract of 127 specimens and found 76 individuals infected with at least one endoparasite, represented by 17 taxa of helminths: two Acanthocephala, three Cestoda, and 12 Nematoda. With our results, knowledge about hidden biodiversity is expanded, particularly as this is a pioneering study regarding the helminth fauna of B. erythromelas. We also describe the occurrence of the species Physaloptera lutzi Cristofaro, Guimarães & Rodrigues, 1976 and Parapharyngodon hispidus Ferreita et al., 2021 for the first time in snakes.